Assessment of Greenhouse Gas Emissions from Different Land-Use Systems: A Case Study of CO2 in the Southern Zone of Ghana. (5th April 2018) - MacCarthy, Dilys Sefakor; Zougmoré, Robert B.; Akponikpè, Pierre Bienvenu Irénikatché; Koomson, Eric; Savadogo, Patrice; Adiku, Samuel Godfried Kwasi
Abstract : The emission of greenhouse gases (GHGs) results in global warming and climate change. The extent to which developing countries contribute to GHG emissions is not well known. This study reports findings on the effects of different land-use systems on GHG emissions (CO2 in this case) from two locations in the southern zone of Ghana, West Africa. Site one (located at Kpong) contained a heavy clay soil while site two (located at Legon) contained a light-textured sandy soil. Land-use systems include cattle kraals, natural forests, cultivated maize fields, and rice paddy fields at site one, and natural forest, woodlots, and cultivated soya bean fields at site two. CO2 emissions were measured using the gas entrapment method (PVC chambers). Trapping solutions were changed every 12–48 h and measurement lasted 9 to 15 days depending on the site. We found that, for the same land-use, CO2 emissions were higher on the clay soil (Kpong) than the sandy soil (Legon). In the clay soil environment, the highest average CO2 emission was observed from the cattle kraal (256.7 mg·m −2 ·h −1 ), followed by the forest (146.0 mg·m −2 ·h −1 ) and rice paddy (140.6 mg·m −2 ·h −1 ) field. The lowest average emission was observed for maize cropped land (112.0 mg·m −2 ·h −1 ). In the sandy soil environment, the highest average CO2 emission was observed from soya cropped land (52.5 mg·m −2 ·h −1 ), followed by the forest (47.4 mg·m −2 ·h −1 ) and woodlot (33.7 mg·m −2 ·h −1 ). Several factors influenced CO2 emissions from the different land-use systems. These include the inherent properties of the soils such as texture, temperature, and moisture content, which influenced CO2 production through their effect on soil microbial activity and root respiration. Practices that reduce CO2 emissions are likely to promote carbon sequestration, which will consequently maintain or increase crop productivity and thereby improve global or regional food security.